Applications of Colorimeter in Machine Visions for Checking Printed-Circuit Boards - Tantaswadi, P.; Serisathien, P.; Voravichayavivat, R.; Sriwanyong, C. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Application of colorimetry in color identification for checking printed-circuit boards (PCBs) is proposed. Inspection of electronic components during the assembly of the printed circuit boards (PCBs) can be done by an analysis of color image. This method significantly enchances the imahe-processing speed. Additionally, the inspection accuracy can be attained by the use of color isodiscrimination contour criterio. Keywords: colorimetry, machine vision, automated visual inspections, isodiscrimination contour, and color identification Corresponding author: E-mail: cast@kmitl.ac.th